A Glutaredoxin, Encoded by the G4L Gene of Vaccinia Virus, Is Essential for Virion Morphogenesis - White, Christine L. (American Society for Microbiology, 2000)
Vaccinia virus encodes two glutaredoxins, O2L and G4L, both of which exhibit thioltransferase and dehydroascorbate reductase activities in vitro. Although O2L was previously found to be dispensable for virus replication, we now show that G4L is necessary for virion morphogenesis. RNase protection and Western blotting assays indicated that G4L was expressed at late times after infection and was incorporated into mature virus particles. Attempts to isolate a mutant virus with a deleted G4L gene were unsuccessful, suggesting that the protein was required for virus replication. This interpretation was confirmed by the construction and characterization of a conditional lethal recombinant virus with an inducible copy of the G4L gene replacing the original one. Expression of G4L was proportional to the concentration of inducer, and the amount of glutaredoxin could be varied from barely detectable to greater than normal amounts of protein. Immunogold labeling revealed that the induced G4L protein was associated with immature and mature virions and adjacent cytoplasmic depots. In the absence of inducer, the production of infectious virus was severely inhibited, though viral late protein synthesis appeared unaffected except for decreased maturation-dependent proteolytic processing of certain core components. Electron microscopy of cells infected under nonpermissive conditions revealed an accumulation of crescent membranes on the periphery of electron-dense globular masses but few mature particles. We concluded that the two glutaredoxin homologs encoded by vaccinia virus have different functions and that G4L has a role in virion morphogenesis, perhaps by acting as a redox protein.